2016
DOI: 10.1016/j.str.2016.06.010
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Crystallography: Reliable and Efficient Identification of Fragment Hits

Abstract: Today the identification of lead structures for drug development often starts from small fragment-like molecules raising the chances to find compounds that successfully pass clinical trials. At the heart of the screening for fragments binding to a specific target, crystallography delivers structural information essential for subsequent drug design. While it is common to search for bound ligands in electron densities calculated directly after an initial refinement cycle, we raise the important question whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 45 publications
3
84
0
3
Order By: Relevance
“…When lowering the temperature to 100 K during X-ray diffraction experiments, W2 was found to be rather H-bonded to W1 than to W3 (occupancies of 75 and 25% in our structure with PDB-code 5MNE). To analyze whether this temperature effect is relevant, we collected three additional X-ray diffraction data sets from non-deuterated uncomplexed trypsin crystals each at 295 and 100 K. All structures were equally processed via an automated refinement pipeline 20 , which places one W2 molecule into the center of the corresponding electron density feature. The resulting structures confirmed that the water pattern in the S 1 pocket differs at the two temperatures with W2 being much closer (by 0.4 Å) to W1 at 100 K (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…When lowering the temperature to 100 K during X-ray diffraction experiments, W2 was found to be rather H-bonded to W1 than to W3 (occupancies of 75 and 25% in our structure with PDB-code 5MNE). To analyze whether this temperature effect is relevant, we collected three additional X-ray diffraction data sets from non-deuterated uncomplexed trypsin crystals each at 295 and 100 K. All structures were equally processed via an automated refinement pipeline 20 , which places one W2 molecule into the center of the corresponding electron density feature. The resulting structures confirmed that the water pattern in the S 1 pocket differs at the two temperatures with W2 being much closer (by 0.4 Å) to W1 at 100 K (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…c Temperature-dependent change in the Asp189 solvation pattern. Four individual X-ray structures of uncomplexed trypsin at cryogenic temperature that were determined via an automated refinement pipeline are shown in blue 20 . The data for these structures have been collected from one deuterated and three non-deuterated crystals.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another recent trend in structural biology focuses on complex structures between proteins or between proteins and chemical compounds (25). To support analyses and modeling of complex structures, we have added HOMCOS (26), a tool for searching, analyzing and modeling of complex structures based on structural similarities.…”
Section: Analysis Tools For Large And/or Complex Structuresmentioning
confidence: 99%